Scrolling to Believe: Evaluating the Link between Perceived Credibility of Social Media as a Source of Political Information and the Political Attitudes of Young Adults in Malaysia - Jamali, Bujang Sanawi; Ernisa, Marzuki (UKM Press (Universiti Kebangsaan Malaysia Publisher)., 2025)
This study examines the dynamic interplay of the perceived credibility of social media as a source of political information and political attitudes among young adults in Malaysia, in the wake of the Undi-18 electoral policy. Conducted through a structured survey of 221 respondents aged 19 to 30, the respondents’ levels of perceived credibility of social media, their levels of political efficacy, and their levels of political cynicism were quantitatively measured. From the analysis, it was found that the respondents exhibited a moderate level of trust in social media as a source of political information, suggesting a cautious approach to its use. However, the more social media is perceived as a credible source of political information, the higher the likelihood of respondents having high political efficacy. The perceived credibility of social media was found to have a negative correlation with political cynicism, suggesting that young adults place greater trust in the reliability of social media as a source of political information, they are less likely to experience feelings of distrust and apathy toward politics. The study also found that political efficacy was inversely correlated with political cynicism, indicating that enhancing political efficacy among the young adults could diminish their cynical attitudes towards politics. Enhancing the regulations and coordination of social media platforms to ensure the dissemination of accurate and balanced political information can therefore foster greater trust in these platforms, strengthen users’ sense of political efficacy, and ultimately, reduce levels of political cynicism.